Divergences and challenges in the negotiation of the global plastics treaty: China’s pathway in advancing global ocean plastic pollution governance - He, Sai; He, Xinlong (Frontiers in Marine Science, 2025)
The current international legal framework for addressing marine plastic pollution is fragmented and lacks binding legal force, making it insufficient to meet the demands of marine plastic pollution governance. Although the international community generally recognizes the necessity of establishing a Global Plastics Treaty, the second part of the fifth session of the Intergovernmental Negotiating Committee (INC-5.2) in 2025 still failed to finalize the treaty text. This study adopts a text analysis approach, focusing on the latest Chair’s Text produced during INC-5.2, which reveals that significant disagreements persist among countries on key issues, including the treaty’s scope of regulation, funding mechanisms, and legal enforceability. As a major global producer and consumer of plastics, China holds significant influence in shaping plastics governance. These disagreements pose challenges for China in terms of normative leadership, funding contributions, and the implementation of governance principles in addressing marine plastic pollution. China can prioritize strengthening regional cooperative governance, providing regional experiences that support the negotiation and implementation of binding provisions under the Global Plastics Treaty, thereby enhancing the institutional leadership. In terms of funding mechanisms, China can act as a bridge to coordinate interests among different groups of countries, promote the implementation of the principle of common but differentiated responsibilities, and expand funding sources through mechanisms such as BRICS. Finally, China can reinforce the promotion of governance concepts, translating them into concrete systems and practices to enhance its soft power, strengthen its voice in marine plastic pollution governance, and offer Chinese approach to this global issue.